SGLT2 Inhibitors Decrease Overhydration and Proteasuria in Patients with Chronic Kidney Disease: A Longitudinal Observational Study - Anja Schork; Marie-Luise Eberbach; Bernhard N. Bohnert; Matthias Wörn; David J. Heister; Felix Eisinger; Elisabeth Vogel; Nils Heyne; Andreas L. Birkenfeld; Ferruh Artunc (Karger Publishers, 2024)
Introduction: SGLT2 inhibitors are used to reduce the risk of progression of chronic kidney disease (CKD). In patients with type 2 diabetes, they have been found to reduce extracellular volume. Given the high prevalence of extracellular volume expansion and overhydration (OH) in CKD, we investigated whether SGLT2 inhibitors might correct these disturbances in CKD patients. Methods: CKD patients who started treatment with an SGLT2 inhibitor were investigated in this prospective observational study for 6 months. Body composition and fluid status were measured by bioimpedance spectroscopy. In addition, spot urine samples were analyzed for albuminuria, glucosuria, and urinary aprotinin-sensitive serine protease activity. Results: Forty-two patients (29% with diabetic/hypertensive CKD, 31% with IgA nephropathy; 88% dapagliflozin 10 mg, 10% dapagliflozin 5 mg, 2% empagliflozin 20 mg; median eGFR 46 mL/min/1.73 m2 and albuminuria 1,911 mg/g creatinine) participated in the study. Median glucosuria increased to 14 (10-19) g/g creatinine. At baseline, patients displayed OH with +0.4 (−0.2 to 2.2) L/1.73 m2, which decreased by 0.5 (0.1-1.2) L/1.73 m2 after 6 months. Decrease of OH correlated with higher OH at BL, decrease of albuminuria, glucosuria, and urinary aprotinin-sensitive protease activity. Adipose tissue mass was not significantly reduced after 6 months. Conclusion: SGLT2 inhibitors reduce OH in patients with CKD, which is pronounced in the presence of high albuminuria, glucosuria, and urinary aprotinin-sensitive protease activity.